Foreign Exchange Exposure Management Practices by Zimbabwe’s Tourism and Hospitality Companies: A Case for the Depreciation of Rand (2014-2016) - Mawanza, Wilford (Journal of Economics and Behavioral Studies, 2016)
One of the key challenges for tourism and hospitality in the Sub-Sahara Africa (SSA) region is currency behaviours and Exchange rate regime choices. When a company engages in international business foreign currency risk management becomes a crucial part of doing business and the tourism industry of Zimbabwe was not spared on this issue. The objective of this research was to assess the foreign exchange (forex) Exposure Management Practices by Zimbabwe’s tourism and hospitality companies. The study was done through a survey on 28 operators in Zimbabwe. A qualitative research approach was adopted in analysis of the data It was found out that the most commonly used ways of reducing the exposure by Zimbabwe’s tourism companies were the amicable and mixed-method approaches, of receiving the currency and use it in the country of origin to import materials, matching receipts and payments in foreign currency, risk shifting though it come with low volumes and compromised repeat business. The study recommended that companies and the entire economy must consider invoicing products and services in Rands and even use the rand as a reporting currency. If for example tourism and hospitality players would price regional tourists especially from South Africa and other Rand countries, ignoring the impact of rand depreciation, it would mean that Zimbabwe’s tourism and hospitality providers will be in direct competition with the former’s own local service providers based on rand priced packages.